Yolk-shell Fe2O3 ⊙ C composites anchored on MWNTs with enhanced lithium and sodium storage - Feng, Zhenxing (2015)
A unique architecture with yolk–shell Fe2O3 ⊙ C composites attached to the surface of MWNTs is designed. Beneﬁting from the good electrical conductivity of MWNTs and carbon layers, as well as the large void space to accommodate the volume expansion/extraction of Fe2O3 during battery cycling, the obtained MWNT@Fe2O3 ⊙ C exhibited outstanding lithium and sodium storage performance.